Simulation of interface behavior between FRP bars and concrete by an elastic-plastic theory via FEM - BRISOTTO,D. S. (2018)
Abstract An elastic-plastic behavior is considered to simulate the interface rupture between grooved, helical wrapped and sand coated helical wrapped bars made of Fiber Reinforced Polymer (FRP) and concrete. Interface properties are obtained comparing results of the model with pull-out experiments. Properties obtained related to grooved bars are similar to properties known for ribbed steel bars. In this case, interface rupture behavior does not depend on bar properties. In case of both helical wrapped bars, on the other side, interface behavior is actually changed by FRP bar characteristics. The advantage of the present formulation is its capability to calculate splitting tractions, responsible for bulk concrete failure.